Competence of Internal Auditors in Higher Education - Hamengkubuwono Hamengkubuwono (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to analyze the independence and competence of internal auditors in improving audit quality results. In the quality management cycle, the role of both external and internal auditors cannot be separated. The Auditor Activity Report provides various feedback for improvement. Because auditors must have the required competencies. There are 45 minimum competencies that auditors at Institut Agama Islam Negeri Curup must possess. From the research findings, there are several competencies that have not been mastered optimally, namely the ability to explain concepts or ideas orally or in writing clearly and fluently, have not attended training at least once a semester, managing audit management, innovative, professional, systematic nature, understanding of definition and terms of quality requirements and understanding of measurement, analysis and improvement.